PENGARUH PROMOSI MEDIA SOSIAL INSTAGRAM DAN WORD OF MOUTH TERHADAP KEPUTUSAH PEMILIHAN PROGRAM STUDI MAHASISWA BARU DI INSTITUT STIAMI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The STIAMI Institute of Social Sciences and Management, as one of the private universities under LLDIKTI Region III Jakarta, utilizes Instagram social media as a digital promotion tool and relies on the power of Word of Mouth from students and alumni to reach prospective new students. Despite various strategies being implemented, data shows fluctuations in the number of new students over the past three years, indicating the need for an evaluation of the effectiveness of these strategies. This study aims to analyze the influence of Instagram social media promotion and Word of Mouth on the decision-making process of new students in choosing a study program at STIAMI Institute. The research method employed in this study is descriptive quantitative research using accidental sampling. The sample consists of 95 new students from STIAMI Institute 2024, drawn from a population of 1,788. The results indicate that Instagram social media promotion and Word of Mouth have a positive influence on the decision-making process for choosing a study program, with a t-value of 13.950 > t-table 1.986 and a significance level of 0.000 < 0.05. The variable of Instagram social media promotion has a coefficient of determination of 67.7%, while Word of Mouth has a t-value of 15.292 > t-table 1.986 and a significance level of 0.000 < 0.05, with a coefficient of determination of 71.5%. The F-value is 166.905 > F-table 3.10, with a significance level of 0.000 < 0.05, and a coefficient of determination of 78.4%.